2014
DOI: 10.1021/jp409627p
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Study on the Metal–Support Interaction between Ru Cluster and Anatase TiO2(101) Surface

Abstract: Density functional theory (DFT) calculations were carried out to study the nucleation and growth mechanism of Ru clusters on the TiO 2 (101) surface by using supported Ru n (n = 1−10, 20, 22) cluster models to understand the metal−support interaction and the resulting catalytic performance toward CO oxidation. The results show that the Ru n cluster prefers a 3D geometry when n ≥ 4 and that the Ru−TiO 2 interface is predominantly composed of Ru−O and Ti−O bonds. Calculation studies based on the density of state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 72 publications
9
59
0
Order By: Relevance
“…Aer relaxation, the atoms adopted a Ni(111)-facetted tetrahedron shape on the zirconia surface. Similar studies 20,49 have shown the preference of aggregation of metal clusters on oxide surfaces. For example, Zhang et al 49 have shown that for n $ 4 Ru n adopts a 3-D geometry on TiO 2 (101), whereas Rajesh et al 20 have shown that the aggregation of Au atoms is more favourable than wetting the Al 2 O 3 surface.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Aer relaxation, the atoms adopted a Ni(111)-facetted tetrahedron shape on the zirconia surface. Similar studies 20,49 have shown the preference of aggregation of metal clusters on oxide surfaces. For example, Zhang et al 49 have shown that for n $ 4 Ru n adopts a 3-D geometry on TiO 2 (101), whereas Rajesh et al 20 have shown that the aggregation of Au atoms is more favourable than wetting the Al 2 O 3 surface.…”
Section: Resultssupporting
confidence: 70%
“…Similar studies 20,49 have shown the preference of aggregation of metal clusters on oxide surfaces. For example, Zhang et al 49 have shown that for n $ 4 Ru n adopts a 3-D geometry on TiO 2 (101), whereas Rajesh et al 20 have shown that the aggregation of Au atoms is more favourable than wetting the Al 2 O 3 surface. The analysis of the interfacial distances in the Ni 6 /ZrO 2 (111) system shows that each Ni atom is at $1.9Å from its nearest O u neighbour.…”
Section: Resultssupporting
confidence: 70%
“…For the transition metal atom/clusters deposited on oxide/hydroxide supports, the model of a heterogeneous catalyst is adopted by a supported metal cluster on the oxide/hydroxide surfaces, which has been generally accepted for understanding the metal-support interaction in many theoretical studies. [48][49][50][51] Here, a periodic surface of Pd-Ni(OH) 2 was modeled by a two-layer Ni(OH) 2 (001) slab with a (5 3 5) unit cell and a threelayer Pd cluster containing 19 Pd atoms placed on this slab ( Figure S38).…”
Section: Density Functional Theory Calculations Of Fa Decompositionmentioning
confidence: 99%
“…E ads is defined as: 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 11 the results found by Zhang et al on the same system. 62 The adsorption mode is characterized by a covalent-polar bond with partial depletion of the electronic charge from Ru which, according to the Bader analysis, has a charge q = +0.6 |e|, Table 2. However, formation of Ti 3+ ions is not observed as shown by both the pDOS curves, Figure 4(b) and (c), and the spin density plots, Figure 5(a).…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%